The development of robust and fast response control algorithm for UAV crop duster - Abas, M. F.; Ahmad, Hamzah; Saad, N. Md; Pebrianti, Dwi; Mohd Rizal, Arshad (2019)
In realizing a high crop yield/year, the possibility of deploying a highly robust, fast response with gimbal lock problem free controller in an underactuated unmanned system is a possibility. The gimbal lock problem is solved via UAV model and control using quaternion angle instead of cartesian angle. By evaluating quatemion UA V model, nonlinear P2 controller is used as the robust control. Original P2 controller is upgraded to include optimize gain which has been optimize using GA. Based on the simulation result, the controller has promising result.